The role of the habenula in drug addiction - Velasquez, Kenia M.; Molfese, David L.; Salas, Ramiro (Frontiers in Human Neuroscience, 2014)
Interest in the habenula has greatly increased in recent years. The habenula is a small brain structure located posterior to the thalamus and adjacent to the third ventricle. Despite its small size, the habenula can be divided into medial (MHb) and lateral (LHb) nuclei that are anatomically and transcriptionally distinct. The habenula receives inputs from the limbic system and basal ganglia primarily via the stria medullaris. The fasciculus retroflexus is the primary habenular output from the habenula to the midbrain and governs release of glutamate onto gabaergic cells in the rostromedial tegmental nucleus (RMTg) and onto the interpeduncular nucleus (IPN). The resulting GABA released from RMTg neurons inactivates dopaminergic cells in the ventral tegmental area (VTA)/substantia nigra compacta (SNc). Through this process, the habenula controls dopamine levels in the striatum. Thus, the habenula plays a critical role in reward and reward-associated learning. The LHb also modulates serotonin levels and norepinephrine release, while the MHb modulates acetylcholine. The habenula is a critical crossroad that influences the brain’s response to pain, stress, anxiety, sleep, and reward. Dysfunction of the habenula has been linked to depression, schizophrenia, and the effects of drugs of abuse. This review focuses on the possible relationships between the habenula and drug abuse.